Angiotensin II type 2 receptor mediates sex differences in mice renal interlobar arteries response to angiotensin II - Viegas, Vinicius U.; Liu, Zhi Zhao; Zavaritskaya, Olga (Journal of hypertension, 2012)
Objective: Functional sex differences are described in several vascular beds. In the case of renal vessels, sex differences could influence processes like regulation of blood pressure and ion balance. Angiotensin II and nitric oxide are important regulators of renal vascular tone. Females have higher nitric oxide synthase expression, nitric oxide bioavailability and ratio of angiotensin II type 2/type 1 receptors. Thus, our objective was to examine whether renal interlobar arteries present sex differences in their response to angiotensin II, and whether angiotensin II type 2 receptors play a role in such differences. - Methods: We investigated the isometric contraction and relaxation of interlobar arteries from female and male mice under blockade of nitric oxide synthases and angiotensin II type 2 receptors. We also investigated the expression of angiotensin II receptors (type 1 and 2) and endothelial nitric oxide synthase. - Results: Significantly less intense contraction to angiotensin II were seen in arteries from females in comparison to male mice. Inhibition of nitric oxide synthases and endothelial removal abolished this difference. Angiotensin II type 2 receptors blockade enhanced contraction to angiotensin II in females, but not in males. Endothelial-dependent vasodilation was more dependent on nitric oxide in females than in males. Expression of angiotensin II type 1 and type 2 receptors was similar between sexes. Expression of endothelial nitric oxide synthase was higher in females. - Conclusion: A sex-specific, nitric oxide-mediated effect via angiotensin II type 2 receptors underlies the sex differences in the response of interlobar arteries to angiotensin II. Our findings may help understanding sex differences in renal hemodynamics and blood pressure control.